Method for estimating the complexity of designing business information systems - Poščić, Patrizia; Pavlić, Mile; Vrček, Neven (2008)
Summary: The most used method for determining the complexity of information systems is the function point method. This paper illustrates the new method, Data on Document (DOD) for estimating the complexity of designing business information systems. Similar methods are shown in brief. The objective is to explain the reasons for using the newly defined DOD method instead of the function point method. The new method is easier to use while the usage of function point method takes a lot of time and effort, and is more complex. The DOD method is compared to the function point method. A high degree of correlation was determined in observed information systems. The DOD method helps in early stages of the development of information systems, when it is not possible to apply the function point method
Bibliografija: 15 jed
Keywords: Informacijski sustavi -- Menadžment